Process Modelling of Friction Stir Welding of Aluminium Alloys AA6061 and aa5083 - Mohd Hatta, Nor Shafiena; Shamsudin, Shazarel (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Friction stir welding (FSW) is a solid-state joining technique that is used to weld many kinds of materials, such as aluminium, magnesium and titanium alloys and even plastics. DEFORM-3D software was used to simulate the FSW process from the experimental research. Input parameters of the tool was obtained from the previous experimental data. The process parameters involved were 700 rpm and 1400 rpm for rotational speed while for transverse speed, settings of 80, 60, and 40 mm/min were applied. The simulations used input parameters that resulted in maximum, medium, and minimum tensile strength in actual experiments performed. Workpiece is defined as rigid-visco plastic material and tool is modelled as rigid because the yield strength of tool material is much higher compared to workpiece materials. The workpieces were meshed with 32000 elements and the tool was meshed with 8000 elements. Remeshing was done at the workpiece and tool contact area along the welding direction to obtain high result accuracy. Boundary conditions and heat transfer coefficient for this FSW process were obtain from previous research paper. Temperature, effective strain, and effective stress distribution during the process on the workpiece were analysed in this study since it cannot be retrieved from the experiment. The results from simulations for different rotational speed and transverse speed showed uneven temperature distribution on the workpieces. These results are not reached agreement with previous research and effected the effective strain and stress distribution. It was observed that caused by deficiency in simulation setup especially for boundary condition setup.